2009
DOI: 10.1007/s12011-009-8496-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Elements in the Anterior Commissures and the Relationships Among their Elements

Abstract: To elucidate compositional changes of the anterior commissure with aging, the authors investigated age-related changes of elements in the anterior commissures and the relationships among their elements. After ordinary dissection at Nara Medical University was finished, the anterior commissures were resected from 45 subjects, ranging in age from 70 to 101 years. The subjects consisted of 22 men and 23 women. After ashing with nitric acid and perchloric acid, the element content of the anterior commissures was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
0
12
1
Order By: Relevance
“…The authors previously investigated age-related changes of elements in the corpora callosa [1] and anterior commissures [2] of the white matter and the pineal bodies [3], olfactory bulbs and tracts [4], and mammillary bodies [5] of the gray matter. It was found that a very high accumulation of Ca and P occurred in the pineal body at old age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors previously investigated age-related changes of elements in the corpora callosa [1] and anterior commissures [2] of the white matter and the pineal bodies [3], olfactory bulbs and tracts [4], and mammillary bodies [5] of the gray matter. It was found that a very high accumulation of Ca and P occurred in the pineal body at old age.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison in Elements with Significant Correlation Among Eight Brain Regions Table 5 indicates elements with significant correlation in the corpus callosum [1], anterior commissure [2], and fornix of the white matter and the pineal body [3], olfactory bulb and [4], mammillary body [5], hippocampus, and dentate gyrus of the gray matter. Significant correlations were found between Ca and P contents, between Ca and Mg contents, between P and Mg contents, and between Ca and Na contents in more than five out of the eight brain regions.…”
Section: Relationships Among Element Contentsmentioning
confidence: 99%
“…In serum, it has been documented for Cu by Ghayour-Mobarhan et al (2005) and Kouremenou-Dona et al (2006); for Se by Lopes et al (2004). In brain, Markesbery et al (1984), Ongkana et al (2010) and Tohno et al (2010)  data converted from nmol/L Table 6. Manganese in Controls and Patients (µg/L) elements.…”
Section: Agementioning
confidence: 99%
“…For changes of Se, Cu and Zn in serum, see Lopes et al (2004) and Ghayour-Mobarhan et al (2005). For Zn variations in brain, see Ongkana et al (2010). Regarding CSF, Bocca et al (2006) noticed lesser Fe amounts in PD males than in females, whereas the opposite was found in controls.…”
Section: Gendermentioning
confidence: 99%
“…To elucidate compositional changes of the brain with aging, the authors previously investigated age-related changes of elements in the corpus callosum [1] and anterior commissure [2] of the white matter and in the pineal body [3], olfactory bulb and tract [4], and mammillary body [5] of the gray matter.…”
Section: Introductionmentioning
confidence: 99%